Modern sniper rifles in the armament of the Serbian Armed Forces - Janković, Darko D.; Vasiljević, Darko M.; Tomić, Ljubiša D.; Duvnjak, Srđan J. (Vojnotehnički glasnik / Military Technical Courier, 2019)
The paper describes sniper rifles and optical sights in use in the Serbian Armed Forces. For the purpose of possible design of an optical sight that would meet modern technical and technological standards and needs of the Serbian Armed Forces, the paper analyzes the optical and mechanical characteristics of the aforementioned.